2001
DOI: 10.1021/ac010615u
|View full text |Cite
|
Sign up to set email alerts
|

A Group Separation Method for Ruthenium, Palladium, Rhenium, Osmium, Iridium, and Platinum Using Their Bromo Complexes and an Anion Exchange Resin

Abstract: A new group separation method for Re and PGE (Ru, Pd, Os, Ir, Pt) is described using a novel anion exchange chromatographic resin called TEVA. Re and PGEs are converted into bromo complexes by heating with HF-HBr mixture in a Teflon bomb at 518 K, by in situ-generated Br2 formed by reaction of HBr and HNO3. Distribution coefficients (Kd) of the bromo complexes onto TEVA resin in 0.1 M HBr with heating at 353 K for one night were 2,200, 16,000, 1,600, 5,500, 4,000, and 17,000 for Ru, Pd, Re, Os, Ir, and Pt, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 29 publications
0
21
1
Order By: Relevance
“…The obtained result shows that the developed SPE method could be applied to the preconcentration of iridium from real samples such as water and soil samples without matrix interference. Solid-phase extraction Inductively coupled plasma-mass spectrometry 0.24 ng mL −1 Environmental and geological samples Dai et al (2000) Flow injection solid-phase extraction Flame atomic absorption spectrometry 0.11 μg mL −1 Synthetic mixture corresponding Di and Davey (1995) Solid-phase extraction UV-vis 20 μg L −1 Synthetic mixture corresponding Taher et al (1997) Solid-phase extraction ICP-MS -Geological samples Makishima et al (2001) Electroanalytical technique Stripping voltammetry 9.10 −7 mol L −1 -Svancara et al (2007) Solid-phase extraction UV-vis spectrophotometry 0.039 μg L −1 Water and soil samples This work…”
Section: Discussionmentioning
confidence: 99%
“…The obtained result shows that the developed SPE method could be applied to the preconcentration of iridium from real samples such as water and soil samples without matrix interference. Solid-phase extraction Inductively coupled plasma-mass spectrometry 0.24 ng mL −1 Environmental and geological samples Dai et al (2000) Flow injection solid-phase extraction Flame atomic absorption spectrometry 0.11 μg mL −1 Synthetic mixture corresponding Di and Davey (1995) Solid-phase extraction UV-vis 20 μg L −1 Synthetic mixture corresponding Taher et al (1997) Solid-phase extraction ICP-MS -Geological samples Makishima et al (2001) Electroanalytical technique Stripping voltammetry 9.10 −7 mol L −1 -Svancara et al (2007) Solid-phase extraction UV-vis spectrophotometry 0.039 μg L −1 Water and soil samples This work…”
Section: Discussionmentioning
confidence: 99%
“…New publications on Au and PGM ions are regularly appearing [82,89,[97][98][99][100][101][102]. Noble metals are most often sorbed as their chloride complexes and (rarer) as bromide complexes [97]. Most sorbents are selective to Au(III), Pd(II), and Pt(IV).…”
Section: N-containing Sorbents For Preconcentration Of Au Pd and Ptmentioning
confidence: 99%
“…Makishima et al 19 decomposed 0.2 g of peridotite with HF-HBr in a Teflon bomb at 245 C, removed insoluble fluorides by centrifugation, and collected Ru, Pd, Os, Ir, Pt (PGEs) and Re from the supernatant with anion exchange chromatography. In this digestion, PGEs and Re are considered to be mixtures of fluoro-and bromo-complexes.…”
Section: ·2 Coprecipitation Of Fluorophile/oxophile Elementsmentioning
confidence: 99%
“…Makishima and Nakamura 19,30 developed a determination method of Ru, Pd, Os, Ir and Pt as well as 187 Os/ 188 Os isotope ratios in silicate samples using reductive digestion with HF-HBr in a Teflon bomb. However, it was found that highly refractory metal phases are not completely dissolved by the reductive digestion.…”
Section: Determination Of Volatile Elementsmentioning
confidence: 99%